Three new species of cave Troglopedetes (Collembola, Paronellidae, Troglopedetinae) from Thailand, with a key to the Thai species - Katthaleeya Surakhamhaeng (Pensoft Publishers, 2021)
Thailand is today the richest country for the genus Troglopedetes Joseph, 1872, with 17 species described from the country. In this study three troglomorphic new species are described from caves in the western region. They are T. spectabilis sp. nov. and T. rungsimae sp. nov. from Kanchanaburi province and T. takensis sp. nov., from Tak province. The three new species share elongated antennae and have the same number of central mac on Th. III and Abd. IV. However, they differ from one another by the combination of: presence of eyes, antennal length, claw morphology, central head macrochaetotaxy and internal row of dental spines. Troglopedetes spectabilis sp. nov. is remarkably different from its congeners by its extreme long appendages, especially the antennae (ratio antenna: head = 5.5). In the second part of the paper the arrangment of antennal chaetotaxy and the diversity of its phaneres is analyzed in the three new species, homologized and compared with those of two other species described from Thailand (T. meridionalis and T. kae). A total of 22 types of chaetae have now been recognized among the species. A new type of S-chaetae for the genus was discovered in this study. There are 5 types of ordinary chaetae, 15 types of S-chaetae, the subapical organite of Ant. IV and scales. A total of 1,107 to 2,183 antennal chaetae on each side were observed, which includes 308–485 S-chaetae, 687–1,402 ordinary chaetae, 72–295 scales and a subapical organite.